Environmental commitment and innovation as catalysts for export performance in family firms - Yacine Haddoud, Mohamed (2021)
Recognizing the extent of inconclusive findings in the environmental commitment – export performance nexus, this study examines this link in order to reduce theoretical ambiguity. The paper focuses on family firms in Poland and assesses the distinct rate of export intensity resulting from strategic commitment to environmental issues, through product innovation and process innovation. Analyzing a sample of 409 firms sourced from the World Bank Enterprise Survey database, the results indicate that strategic commitment to environmental issues encourages process innovation but not product innovation. In turn, process innovation increases export intensity while product innovation does not. It is also found that quality certifications interact with the relationship be tween strategic commitment to environmental issues and product innovation. These findings pose important theoretical implications and offer insights to stakeholders particularly interested in the sustainable practices of family firms.